Exploring English Education Department Students’ Challenges in Adopting IPA for Pronunciation Accuracy - Abraham, Najwa Syah; Safira, Serlina Yulia Alfian; Rohmana, Wahyu Indah Mala (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The difficulties that students in the English Education Department encounter when attempting to accurately pronounce words using the International Phonetic Alphabet (IPA) are examined in this study. Using a descriptive qualitative method, data were collected through questionnaires and interviews with students who were familiar with IPA. Significant challenges are shown by the data, such as trouble connecting symbols to sounds, a lack of practice opportunities, and a lack of instructional tools. Students recognize the value of IPA in enhancing pronunciation in spite of these obstacles, and they indicate a great desire for a more comprehensive and engaging education. To improve IPA education, suggestions include using audio-visual aids, doing more practice sessions, and utilizing collaborative learning techniques. These results offer insightful information for enhancing phonetics instruction and helping students gain self-assurance and pronunciation skills. What makes this study important is its focus on the practical challenges faced by students in mastering IPA, an area that is critical for language educators yet often overlooked in curriculum design. By identifying specific barriers and proposing targeted solutions, this research provides a unique contribution to phonetics instruction. Furthermore, it emphasizes the role of innovative teaching methods in building students' confidence and pronunciation skills, offering a foundation for future studies aimed at bridging the gap between theory and practical application in English education.